Satellite tracking reveals a dichotomy in migration strategies among juvenile loggerhead turtles in the Northwest Atlantic - Mansfield, Katherine L; Saba, Vincent S; Keinath, John A; Musick, John A (Marine biology, 2009)
Few data are available on the movements and behavior of immature Atlantic loggerhead sea turtles (Caretta caretta) from their seasonal neritic foraging grounds within the western north Atlantic. These waters provide developmental habitat for loggerheads originating from several western Atlantic nesting stocks. We examined the long-term movements of 23 immature loggerheads (16 wild-caught and seven headstart turtles) characterizing their seasonal distribution, habitat use, site fidelity, and the oceanographic conditions encountered during their migrations. We identified two movement strategies: (1) a seasonal shelf-constrained north-south migratory pattern; and (2) a year-round oceanic dispersal strategy where turtles travel in the Gulf Stream to the North Atlantic and their northern dispersal is limited by the 10-15°C isotherm. When sea surface temperatures dropped below 20°C, neritic turtles began a migration south of Cape Hatteras, North Carolina (USA) where they established fidelity to the waters between North Carolina's Outer Banks and the western edge of the Gulf Stream along outer continental shelf. Two turtles traveled as far south as Florida. Several turtles returned to their seasonal foraging grounds during subsequent summers. Northern movements were associated with both increased sea surface temperature (>21°C) and increased primary productivity. Our results indicate strong seasonal and interannual philopatry to the waters of Virginia (summer foraging habitat) and North Carolina (winter habitat). We suggest that the waters of Virginia and North Carolina provide important seasonal habitat and serve as a seasonal migratory pathway for immature loggerhead sea turtles. North Carolina's Cape Hatteras acts as a seasonal “migratory bottleneck” for this species; special management consideration should be given to this region. Six turtles spent time farther from the continental shelf. Three entered the Gulf Stream near Cape Hatteras, traveling in the current to the northwest Atlantic. Two of these turtles remained within an oceanic habitat from 1 to 3 years and were associated with mesoscale features and frontal systems. The ability of large benthic subadults to resume an oceanic lifestyle for extended periods indicates plasticity in habitat use and migratory strategies. Therefore, traditional life history models for loggerhead sea turtles should be reevaluated.